Initial experience of Emicizumab prophylaxis in children with inhibitor positive severe hemophilia A from a single center in India - Nita Radhakrishnan; Ravi Shankar; Manideepa Maji; Megha Rana (Elsevier, 2021)
Background: Although improvement in the access to clotting factor concentrates and provision of comprehensive care has dramatically improved the quality of life of patients with severe hemophilia, inhibitor-positive patients still develop significant morbidity in terms of joint involvement, progression to disability and life threatening bleeds due to poor access to bypassing agents and immune tolerance induction. Objective: To analyze the response of patients with severe hemophilia A and high-titer inhibitors started on Emicizumab prophylaxis. Methods: Patients with inhibitor-positive severe Hemophilia A were followed up for bleed frequency, joint involvement and health-related quality-of-life assessment (HR-QOL) using PedHAL questionnaire. The data from 1 year prior to start of Emicizumab or from diagnosis of inhibitor status (if shorter period) was compared to that 4 weeks after start of the drug. Emicizumab was administered as per standard guidelines. Results: 4 patients were initiated on Emicizumab prophylaxis and followed for a median period of 34 weeks (19-57 weeks). The average bleed frequency reduced from 2 to 3.5 per month to 0 after initiation of prophylaxis. No significant adverse events were reported. Improvement in raw and normalized data for all 7 domains of PedHAL which measures activities of daily living was observed. Functional improvement was noted as early as 4 weeks into treatment. Conclusion: Emicizumab is a promising agent for prophylaxis of patients with severe hemophilia A and high titre inhibitors.